The invisible intersectionality of female gender in Thailand's response to the HIV epidemic. Issue 7 (2nd July 2020) - Thaweesit, Suchada; Sciortino, Rosalia
Abstract: This article uses feminist perspectives to analyse Thailand's response to the HIV epidemic from its inception in 1984 until today. In particular, it applies the WHO Gender Responsiveness Assessment Scale to explain how and to what degree gender considerations have been integrated into successive HIV policies and programmes. Findings show that, from 1984 to 1996, HIV prevention policies were generally insensitive to gender and only started to pay limited attention to women's needs between 1997 and 2011. Gender sensitivity increased in the 2012–2019 period, but the focus then was more on 'men who have sex with men' and the transgender communities than on women. In general, Thailand's HIV responses has overlooked gender power relations and the adverse effects of the intersection between women's gender and their other disadvantaged social statuses.